Memelihara Kestabilan Emosional dengan Terapi Emotional Freedom Technique (EFT) di Masa Pandemi Covid–19 - Indah Fajrotuz Zahro; M. Abid Amrullah (TAAWUN, 2021)
The pandemic of covid-19 has impacted many sectors. Millions of people victims this virus and disturb mental health. All of them becase declining income, social distancing and methods that always change. It’s need preventive efford and curative to save healty and emotional. Emotional freedom technique (EFT) is felt appropriately for stabilizing emotions and became simple methods to all generation. Focus on negative emotional problem that sould be addressed by describing problems and typing meridian. the purpose from This activities are for protect emotional stability by Emotional freedom technique. The method used by qualitative phenomology. The subject or client from this EFT is the youth of palembon village, kanor district in the bojonegoro regency. This activity is in the forum of workshop by nine youth of palembon in resident’s house at 9-10 of april 2021. From this workshop, subject get education about EFT and how to applicated it. In the first day, the workshop start from 09.00 AM until 02.00 PM. And in the second day, start from 09.00 AM. Until 12.00 AM. In the third day, any perform devotion to the subject with individual model to put more emphasis on aspects of decency and secrecy, that is on 12 – 13 of April 2021. The problem that arised in the post-crucial of the pandemic is boredom complained regarding education and employment. Use EFT make persons more relaxed and less nervous to do something. The result from this devotion is satisfying results. One use therpy of EFT in the a group and 3 times by personal make the client’s cycle of negative emotional problems has declined significantly.